KETERKAITAN ANTARA KONVERGEN ALMOST SURELY, KONVERGEN DALAM PROBABILITAS, KONVERGEN DALAM MEAN, DAN KONVERGEN DALAM DISTRIBUSI - Agusta, Vira; Putri, Nurweni; Syahrul, Maya Sari (MAp (Mathematics and Applications) Journal, 2019)
Pada penelitian ini mengkaji keterkaitan antara konvergen almost surely, konvergen dalam probabilitas, konvergen dalam mean, dan konvergen dalam distribusi. Jika barisan variabel random  konvergen almost surely ke suatu variabel random X, maka konvergen dalam probabilitas ke variabel random ke X. Jika barisan variabel random  konvergen dalam probabilitas ke variabel random X maka konvergen dalam mean ke  X. Jika barisan variabel random  konvergen dalam probabilitas ke variabel random X maka konvergen dalam distribusi ke X.AbstractIn this research the relations between convergence almost surely, convergence in probability, convergence in mean, and convergence in distribution. If the sequence of random variables  converges almost surely to a random variable X, then it converges in probability to the random variable to X. If the sequence of random variables  converges in probability to a random variable X, then it converges in mean to the random variable to X. If the sequence of random variables  converges in probability to a random variable X, then it converges in the distribution to the random variable to X.